2017
DOI: 10.1089/cap.2016.0207
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blind Placebo-Controlled Trial on Effectiveness and Safety of Celecoxib Adjunctive Therapy in Adolescents with Acute Bipolar Mania

Abstract: Celecoxib may be an effective adjuvant therapy in treatment of manic episodes (without psychotic features) of adolescents with bipolar mood disorder. The mood-stabilizing role of this drug might be mediated through its action on inflammatory cascades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…2) full results could not be obtained despite efforts to contact the authors (Berk et al, 2012, Raghuvanshi et al, 2013, Halaris et al, 2014, Mousavi et al, 2017; 3) they reported results of a secondary analysis of a primary study ; 4) they did not have a placebo/TAU arm (Mohammadinejad et al, 2015). 14 studies were therefore included in the meta-analysis whilst the excluded studies were included in the qualitative analysis.…”
Section: Resultsmentioning
confidence: 99%
“…2) full results could not be obtained despite efforts to contact the authors (Berk et al, 2012, Raghuvanshi et al, 2013, Halaris et al, 2014, Mousavi et al, 2017; 3) they reported results of a secondary analysis of a primary study ; 4) they did not have a placebo/TAU arm (Mohammadinejad et al, 2015). 14 studies were therefore included in the meta-analysis whilst the excluded studies were included in the qualitative analysis.…”
Section: Resultsmentioning
confidence: 99%
“…A 2014 meta‐analysis suggests celecoxib, a selective COX‐2 inhibitor, is effective add‐on therapy in depression (Kohler et al, ). In the years since, celecoxib has shown promise as adjunctive therapy in young manic patients (Arabzadeh et al, ; Mousavi et al, ). Adjunctive celecoxib may also improve symptoms in schizophrenia according to a recent meta‐analysis (W. Zheng et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…In the years since, celecoxib has shown promise as adjunctive therapy in young manic patients (Arabzadeh et al, 2015;Mousavi et al, 2017).…”
Section: Cyclooxygenase-2 Inhibitorsmentioning
confidence: 99%
“…One RCT conducted among a sample of Iranian adolescents with acute mania (without psychotic features) studying the efficacy and safety of celecoxib as an adjuvant therapy showed a statistically significant reduction ( p = 0.04) in Young Mania Rating Scale scores in the intervention group compared with the placebo group at week 8 [43]. …”
Section: Celecoxib As An Adjuvant Treatment Option For Bpad: the Factsmentioning
confidence: 99%
“…However, these studies have limited external validity due to their narrow inclusion criteria. For instance, Mousavi et al [43] recruited only adolescents with acute mania, excluding those with psychosis, and Arabzadeh et al [42] only included manic patients without psychosis. There is a high frequency in the number of occurrences of auditory hallucination, paranoid delusions, and Schneider’s First Rank Symptoms in BPAD (18, 28, and 18%, respectively), with about half of the patients having grandiose delusions [46].…”
Section: Current Treatment Guidelines For Celecoxib In Bpads and Cavementioning
confidence: 99%